Inovasi Layanan JAMILA (Jaminan Layanan Prima Mengantar Buku Andalan Ke Pemustaka) pada Perpustakaan Kota Yogyakarta - Septiara, Dara; Aiman, Nur; Masruri, Anis (Nur Science Institute, 2025)
This study aims to analyze the Jamila service innovation (Guarantee of Excellent Service Delivering Reliable Books to Users) implemented in the Yogyakarta City Library. Jamila service is a form of book delivery service based on